The development and validation of a virtuous leadership scale - Ou, Yang Annie (Department of Civil Engineering, 2022)
There is a need for virtuous leaders that have a sound moral compass that guide their actions and decisions towards good and honourable outcomes. In particular, the current research study responded to a call in literature to address an African context perspective of virtuous leadership. Based on this, the aim was to formulate a theoretical conceptualisation of virtuous leadership that was grounded in an African contextual perspective to develop and validate a Virtuous Leadership Scale (VLS). The current research study was a descriptive research design with a cross-sectional approach. Secondary quantitative data and primary qualitative and quantitative data was utilised by means of convenience sampling strategy and snowball technique. A realised sample for the secondary quantitative data (n = 193) and the primary quantitative data (n = 72) was collected from the general working population. A conceptual/theoretical model of virtuous leadership was proposed, which captured seven virtues that encompassed an African contextual perspective: 1) courage; 2) humanity; 3) humility; 4) integrity; 5) justice; 6) prudence; and 7) temperance. Based on this model, items were generated and analysed prior to the development of the VLS. Exploratory Factor Analysis confirmed the unidimensionality of each virtue subscale. Utilising Confirmatory Factor Analysis, the measurement model was found to be a good fit. Furthermore, empirical evidence of reliability, discriminant and convergent validity was found, however, predictive validity was not supported. The current research study developed a valid and reliable scale that measures the virtuous leadership construct. There are limitations, recommendations and theoretical contributions discussed.